Development of Mind Map-Based Science LKPD for Critical Thinking in Fifth Grade Students at Banyuasin Public Elementary School - Ayu Septyani; Umar Abdullah; Fery Muhamad Firdaus (FKIP - Universitas Riau, 2026)
This study aims to develop a Mind Map–Based Student Worksheet (LKPD) for the IPAS subject to enhance critical thinking skills among fifth-grade students at Banyuasin Public Elementary School. The need for this development emerged from the low level of students' analytical skills and the limitations of existing linear worksheets that do not fully support concept visualization. Using the Research and Development method with the ADDIE model, the product was designed based on curriculum analysis, student characteristics, and learning objectives, followed by expert validation, limited trials, and field implementation. The developed worksheet was validated by experts in material, media, curriculum, and language, achieving an average score of 80%, indicating high validity. Limited trials showed very high practicality, with student responses reaching 85.93% and teacher responses 95%. Field testing involving 31 students demonstrated the effectiveness of the worksheet, marked by a significant improvement between pretest and posttest results (Wilcoxon = –4.898) and an N-gain score of 0.43 in the moderate category. The findings conclude that the Mind Map–Based IPAS LKPD is valid, practical, and effective for supporting structured conceptual understanding and improving students' critical thinking skills.